Synergizing stakeholders’ communication for religious harmony in Indonesia - Ali Ridho; Syahrul Rahmat; Muhammed Sahrin Haji Masri; Idi Warsah (Islamic Communication Journal, 2023)
Inter-religious conflicts are born, among others, due to misunderstandings in receiving and interpreting messages in the process of multi-religious community interaction, without exception conflicts in Bantul Regency, Indonesia. This research uses a qualitative approach that is descriptive analysis with the type of case study method. The results concluded that the conflict was caused by the process of inter-religious communication that took place in a stagnant and closed manner. In the process of communication between religious communities in large numbers, there are influences in the form of differences in religious, socio-cultural, political views to diverse ideologies and involve high psychological emotions.  A religious conflict resolution approach that is oriented towards a transparent model of government policy implementation and reaches all levels of society is an obligation for regional and national leaders. Then, interfaith leaders must prioritize patterns of thinking and behaving by promoting a moderate attitude that puts the human side at the main level compared to group and religious backgrounds. In addition, religious people must be able to put aside egoism and a priori attitudes in interacting with people of other religions and religious leaders are obliged to communicate messages of peace and harmony in the frame of plurality. This study contributes to the development of a communication model in interfaith conflict resolution.***Konflik antar umat beragama lahir antara lain disebabkan oleh kesalahpahaman dalam menerima dan menafsirkan pesan dalam proses interaksi masyarakat multi agama, tanpa terkecuali konflik di Kabupaten Bantul, Indonesia. Penelitian ini menggunakan pendekatan kualitatif yang bersifat deskriptif analisis dengan jenis metode studi kasus. Hasil penelitian menyimpulkan bahwa konflik tersebut disebabkan oleh proses komunikasi antar umat beragama yang berlangsung secara stagnan dan tertutup. Dalam proses komunikasi antar umat beragama dalam jumlah yang banyak tersebut, terdapat pengaruh berupa perbedaan cara pandang agama, sosial budaya, pandangan politik hingga ideologi yang beragam dan melibatkan emosi psikologis yang tinggi.  Pendekatan penyelesaian konflik agama yang berorientasi pada model implementasi kebijakan pemerintah yang transparan dan menjangkau seluruh lapisan masyarakat menjadi kewajiban bagi para pemimpin daerah dan nasional. Kemudian, para pemimpin lintas agama harus mengedepankan pola berpikir dan bersikap dengan mengedepankan sikap moderat yang menempatkan sisi kemanusiaan pada tataran utama dibandingkan dengan latar belakang kelompok dan agama. Selain itu, umat beragama harus mampu mengesampingkan egoisme dan sikap apriori dalam berinteraksi dengan umat beragama lain dan para pemuka agama berkewajiban mengkomunikasikan pesan-pesan perdamaian dan kerukunan dalam bingkai kemajemukan. Studi ini berkontribusi bagi pengembangan model komunikasi dalam penyelesaian konflik antar agama.